Simultaneous path following and lateral stability control of 4WD-4WS autonomous electric vehicles with actuator saturation. (February 2019) - Chen, Te; Chen, Long; Xu, Xing; Cai, Yingfeng; Sun, Xiaoqiang
Highlights: A novel simultaneous path following and lateral stability control method was proposed for four-wheel independent drive and four-wheel independent steering autonomous electric vehicles. A Hamilton-energy-function-based controller was presented for integrated path following and lateral stability control, and the stability and convergence of controller was proved. The actuator constraints were considered in the controller design process. Abstract: A simultaneous path following and lateral stability control method was presented for four-wheel independent drive and four-wheel independent steering (4WD-4WS) autonomous electric vehicles based on Hamilton energy function with the actuator saturation being considered in this paper. The hierarchical control strategy including upper layer controller and lower layer controller is used for simultaneous path following and lateral stability control. In the upper layer controller, the vehicle motion controller is designed using Hamilton energy function control theory and the convergence and stability of controller was proved, the control demand of simultaneous path following and lateral stability was obtained and messaged to the lower layer controller. In the lower layer controller, the orientated tire force allocation method was used to execute the control demand by real-time tire force allocation control of four wheels. The simulations are performed in the CarSim-Simulink co-simulation platform, and the effectiveness of proposed control method was verified.